2017
DOI: 10.21037/jss.2017.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immediate post-operative pain medication on length of hospital stay: does it make a difference?

Abstract: Our study demonstrates that the choice of immediate post-operative pain medication can make a difference in the hospital course for patients. Identifying these types of factors might help increase patient care and reduce health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…A historical cohort study showed that the usage of PCA with morphine decreased the length of stay in hospital compared with hydromorphone. 17 Nevertheless, other small RCTs have shown no significant differences in analgesia or side effect profiles with PCA morphine vs hydromorphone. 18,19 A meta-analysis investigating adverse effects of opioids administered via PCA similarly showed that there were no differences in side effects between morphine and hydromorphone.…”
Section: Discussionmentioning
confidence: 98%
“…A historical cohort study showed that the usage of PCA with morphine decreased the length of stay in hospital compared with hydromorphone. 17 Nevertheless, other small RCTs have shown no significant differences in analgesia or side effect profiles with PCA morphine vs hydromorphone. 18,19 A meta-analysis investigating adverse effects of opioids administered via PCA similarly showed that there were no differences in side effects between morphine and hydromorphone.…”
Section: Discussionmentioning
confidence: 98%
“…This section focuses on the management of uncontrolled perioperative pain, which is not only one of the most consistent risk factors for PPSP44–46 but also possibly the most modifiable. Poorly controlled acute postsurgical pain is associated with harmful outcomes such as PPSP,45 46 108 increased hospital length of stay,109 110 increased risk of postsurgical end-organ injury (eg, oliguria, myocardial injury)109 111 and persistent opioid use 109 112. Because pre-existing chronic pain and preoperative opioid use increase the risk of uncontrolled postsurgical pain,45 46 it stands to reason that decreasing preoperative pain levels and opioid utilization via presurgical medication management may be beneficial.…”
Section: Chronification Of Pain In the Perioperative Settingmentioning
confidence: 99%
“…Elsamadicy et al explored factors contributing to delays in the diagnosis of cervical stenosis and subsequent treatment via elective discectomy and spinal fusion 72 . Considering age, race, sex, and body mass index, only Black race was an independent predictor of increased duration of preoperative pain before surgical treatment 72 .…”
Section: Spinementioning
confidence: 99%
“…Elsamadicy et al explored factors contributing to delays in the diagnosis of cervical stenosis and subsequent treatment via elective discectomy and spinal fusion 72 . Considering age, race, sex, and body mass index, only Black race was an independent predictor of increased duration of preoperative pain before surgical treatment 72 . In the setting of spine trauma surgery, there exists sig-nificant differences in surgical intervention rates between White patients and patients of other races; the latter demonstrated increased lengths of stay, complications, and mortality compared with White patients 79 .…”
Section: Spinementioning
confidence: 99%